Formation and growth of fresh atmospheric aerosols: eight years of aerosol size distribution data from SMEAR II, Hyytiälä, Finland - Dal Maso, M.; Kulmala, M.; Riipinen, I.; Wagner, R.; Hussein, T.; Aalto, P. P.; Lehtinen, K. E. J. (Boreal Environment Research Publishing Board, 2024)
We analyzed size distributions measured continuously at a boreal forest measurement site at Hyytiälä, Finland between 1996 and 2003. From the eight-year data we identified days when new aerosol particle formation was taking place as well as days when no formation was detected, removing days with ambiguous status. The event days were then classified based on whether it was possible to determine formation and growth rates of new particles. These characteristics were then calculated. We found that new particle formation happens frequently in the boreal forest boundary layer, with at least 24% of days containing an event. Events are more probable during spring and autumn than during other times of the year. The average formation rate of particles larger than 3 nm was 0.8 cm–3 s–1, with enhanced rates during spring and autumn. The mean growth rate was 3.0 nm h–1, peaking in summer. The created event database is valuable for future studies of reasons leading to new particle formation in the atmosphere.